2018
DOI: 10.29252/jarums.18.3.341
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Coronary Heart Disease in Iran: A Bottom-up Approach in 2014

Abstract: Background & objectives: cardiovascular diseases are the main cause of mortality around the whole world. However, there is limited information on its economic costs in Iran. The aim of this study was to evaluate the economic costs of coronary heart disease in Iran in 2014. Methods: The diseases costs were calculated based on the incidence approach using a bottomup method and a community-oriented perspective. The drug cost information was obtained from angiographed patients (607 cases) in Shahid Modarres Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies in our country have shown that the average BMI of Iranian adults has increased over the past two decades [ 27 ], and that about 60% of Iranian adults are overweight or obese [ 5 ]. On the other hand, in 2014, CHD contributed more than 16% of whole healthcare financial costs in Iran [ 28 ]. Moreover, healthcare costs has increased substantially in recent years [ 29 ], hence, it is expected that the economic cost of CHD to be much higher now, and will continue to rise for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our country have shown that the average BMI of Iranian adults has increased over the past two decades [ 27 ], and that about 60% of Iranian adults are overweight or obese [ 5 ]. On the other hand, in 2014, CHD contributed more than 16% of whole healthcare financial costs in Iran [ 28 ]. Moreover, healthcare costs has increased substantially in recent years [ 29 ], hence, it is expected that the economic cost of CHD to be much higher now, and will continue to rise for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Direct medical costs, encompassing high blood pressure diagnosis and treatment, along with costs related to selected diseases, Direct medical costs of selected diseases were calculated using health insurance data, survey(26) and a literature review(24, 27, 28), and Direct non-medical costs Using a literature review were calculated (27, 28). and indirect costs were calculated using the human capital approach Using the NASBOD and IHME database for Global Burden of Disease (22, 29).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that CVD is costly in the Iranian health care system. Health policymakers can limit the costs and consequences of the disease by using resources efficiently and effectively and expanding self-care and screening programs (Raghfar et al, 2018). The burden of NCDs is associated with poverty and serves as a barrier in achieving sustainable development goals (Nugent et al, 2018).…”
Section: Economic and Financial Factorsmentioning
confidence: 99%